Periodismo digital y su impacto en la opinión pública de los habitantes del cantón Quevedo, año 2022 - Arias Roz, Melina Jamileth (2022)
The impact that digital journalism is causing in the citizens of the Quevedo canton. After the country suffered an earthquake that shook the coast of Ecuador, the work of the media began to be questioned and their promptness with which the information was issued, based on this phenomenon, which is why this question is generated. . Why did the media not immediately broadcast what happened? And did you have to resort to digital media to be informed? An analysis is carried out to find out what were the real causes of why the media acted slowly, leaving the country in media silence, without instant information. Forcing social networks, Twitter, to take control with unverified photographs, but making known what was happening in the country, especially in ground zero, where the epicenter occurred. The relevance of digital media today for the inhabitants will be pointed out with its impact on the Public Opinions of the inhabitants of the Quevedo Canton in 2021. In this investigation it was possible to analyze digital journalism. What was the impact that it caused in the public opinion of the inhabitants of the Quevedo canton, year 2021. The media were created to satisfy the needs that over time were increasing in the human being, to be able to express themselves and communicate with other people in different places. The development of digital journalism was not easy, they had to discover and have been implemented with the advance of the industrialization revolution. The era of digital journalism has been determined vital today in the face of a society that is advancing, the connectivity of being informed in the midst of world events.